Cost-utility analysis of centrally inserted totally implanted access port (PORT) vs. peripherally inserted central catheter (PICC) in the oncology chemotherapy - Shao, Guoliang; Zhou, Xiaoying; Zhang, Shaoya; Wu, Shuaijun; Dong, Yichen; Dong, Zuojun (Frontiers in Public Health, 2022)
Background Peripherally inserted central catheter (PICC) and centrally inserted totally implanted access port (PORT) are two types of intravenous infusion devices that are widely used in clinical practice. PORTs are more expensive to insert than PICCs but have fewer complications. Two cost-utility analyses of PICCs and PORTs in China have been published, but had conflicting findings. This study aimed to compare the cost-utility of PICCs and PORTs. Methods We conducted a prospective observational trial including 404 patients with cancer and a cross-sectional study to calculate cost and complications of a PICC and PORT. Utility was measured using the EuroQol five-dimensional questionnaire (EQ-5D-5L). A cost-utility analysis was performed from a healthcare system perspective in China. Results The average total cost of PICCs and PORTs were ¥ 4,091.7 and ¥ 4,566.8, which yielded 0.46 and 0.475 quality-adjusted life-years (QALYs) in a 6-month dwell time, respectively. The incremental cost-utility ratio (ICUR) was ¥ 31,670.9 per QALY. A one-way sensitivity analysis showed that the base-case results were robust, and the probabilistic sensitivity analysis showed that at a willingness-to-pay (WTP) threshold of ¥ 80,976 per QALY (China's per capita GDP in 2021) the probability of a PORT being cost-effective was 96%. Conclusion PORTs were more cost-effective than PICCs for a 6 and 12-month dwell time. The total cost for a PORT was also less than that of a PICC. PORT is therefore recommended as a medium to long-term intravenous delivery device in clinical practice.